Molecular mechanisms of ferroptosis and its roles in leukemia - Chen, Zhe; Zheng, Suying; Han, Jiongping; Fu, Leihua; Fu, Jiaping; Zhang, Zhijian; Hong, Pan; Feng, Weiying (Frontiers in Oncology, 2023)
Cell death is a complex process required to maintain homeostasis and occurs when cells are damage or reach end of life. As research progresses, it is apparent that necrosis and apoptosis do not fully explain the whole phenomenon of cell death.Therefore, new death modalities such as autophagic cell death, and ferroptosis have been proposed. In recent years, ferroptosis, a new type of non-apoptotic cell death characterized by iron-dependent lipid peroxidation and reactive oxygen species (ROS) accumulation, has been receiving increasing attention. Ferroptosis can be involved in the pathological processes of many disorders, such as ischemia-reperfusion injury, nervous system diseases, and blood diseases. However, the specific mechanisms by which ferroptosis participates in the occurrence and development of leukemia still need to be more fully and deeply studied. In this review, we present the research progress on the mechanism of ferroptosis and its role in leukemia, to provide new theoretical basis and strategies for the diagnosis and treatment of clinical hematological diseases.